Effects of increasing dietary lysine in transition diets on nursery pig growth performance - J L Usry; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 1,400 weanling pigs (initially 13.6 lb) was used in a 9 d growth assay (d 4 to 13 postweaning) to determine the effects of increasing lysine in the transition diet on nursery pig growth performance. All pigs were fed a common SEW diet until d 4 after weaning. Pigs were then switched to experimental diets with total dietary lysine levels of 1.40, 1.50, 1.60, 1.70 or 1.80%. All diets were formulated to contain 20% soybean meal, with increasing amounts of synthetic amino acids to achieve desired amino acid concentrations in the diets. From d 4 to 9 postweaning, increasing lysine increased ADG (linear, P<0.03) and improved feed efficiency (linear, P<0.001), but ADFI was not affected. Overall (d 4 to 13 postweaning), pigs fed diets containing increasing dietary lysine had improved ADG (linear, P<0.03) and feed efficiency (linear, P<0.001), with no differences in ADFI. Although responses to increasing dietary lysine were linear, there was little improvement either ADG or F/G above 1.7% lysine. There was no difference in average pig weight at the end of the trial, probably because of the short duration of the study. In conclusion, increasing dietary lysine up to 1.7% in transition diets (13 to 19 lb) for nursery pigs maximized growth performance.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Nursery pig; Transition diet; Lysine requirement; Growth; Swine